Determinasi Readmisi Rumah Sakit pada Pasien Acute Coronary Syndrome Ruang Rawat Inap Pusat Jantung - Syahrul, Syahrul; Muhtar, Ahmad Rizal; Said, Syahrani (Mando Care Jurnal, 2025)
Acute Coronary Syndrome (ACS) is a heart disease caused by the disruption of blood flow to the heart, leading to oxygen deficiency. Readmission of ACS patients after hospitalization is common. This study aims to identify factors associated with readmission in ACS patients at the Integrated Heart Center, Dr. Wahidin Sudirohusodo Hospital, Makassar. This quantitative study with a cross-sectional design involved 121 patients. Data were collected using questionnaires to assess medication adherence and physical activity. The results showed that a history of hypertension, diabetes, dyslipidemia, medication adherence, and physical activity were significantly associated with readmission in ACS patients, while age, smoking history, and obesity were not. These findings emphasize the importance of education, therapy adherence, and lifestyle changes to reduce readmissions and improve healthcare quality.